An Energetic Diagnostic of Tropical Cyclone Size in f‐Plane Simulations. (23rd December 2022) - Zhang, Jishi; Lin, Yanluan
Abstract: As a major feature of tropical cyclones (TCs), controlling factors of TC outer size or size scaling remains a fundamental scientific question. The Rossby deformation radius and a natural extent associated with potential intensity have been proposed as two scalings of TC size. But neither of them satisfactorily captures the sensitivity of TC size to sea surface temperature (SST) in idealized f ‐plane simulations. Inspired by the studies of the Hadley circulation, here we proposed a new TC scaling based on an energetic diagnostic scaling. TC size is primarily a ratio of the secondary circulation strength to subsidence velocity, further determined by the total atmospheric heating in the ascending area, the gross moist stability, the diabatic cooling, and the dry static stability. The former two is based on the moist energetic budget applied to the whole storm structure, while the latter two is based on the dry thermodynamic budget applied to the subsidence areas. The new scaling well captured the sensitivity of TC size to SST in idealized f ‐plane simulations, partly resulted from expanded ascending area, increased surface moisture deficit, and weakened subsidence with increased SST. Plain Language Summary: Among the basic quantities of tropical cyclones (TCs), size is probably the most difficult to understand and predict. Due to lack of theories, our understanding of the controlling factors of TC size is rather limited. As a result, we have low confidence about the future change of TC size with warming. Idealized simulations have been used in recent years to study the environmental constraints of TC size, but the conventional scalings cannot capture the strong sensitivity of TC size to sea surface temperature (SST). In this study, we propose an energetic scaling that well predicts the simulated TC size variation with SST. We found that the secondary circulation strength and subsidence velocity essentially constrain the overall extent of TC. In addition, the framework also provides a new perspective to understand the limitation of conventional scalings. Key Points: A new energetic scaling successfully captures the outer size of tropical cyclone (TC) in f ‐plane simulations The strong sensitivity of TC size to sea surface temperature (SST) depends on ascending area, surface moisture deficit, and subsidence velocity Conventional TC size scalings underestimate or neglect the increases in inner‐core heating, which weaken their sensitivities to SST